2013
DOI: 10.3389/fnsys.2013.00021
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced representation of spectral contrasts in the primary auditory cortex

Abstract: The role of early auditory processing may be to extract some elementary features from an acoustic mixture in order to organize the auditory scene. To accomplish this task, the central auditory system may rely on the fact that sensory objects are often composed of spectral edges, i.e., regions where the stimulus energy changes abruptly over frequency. The processing of acoustic stimuli may benefit from a mechanism enhancing the internal representation of spectral edges. While the visual system is thought to rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 119 publications
5
16
1
Order By: Relevance
“…STRFs were obtained from 180-s multitone pip stimuli (Blake and Merzenich 2002;Catz and Noreña 2013;deCharms et al 1998;Gourévitch et al 2009;Noreña et al 2008;Valentine and Eggermont 2004). Tone pips (49 frequencies, 8 frequencies per octave covering 6 octaves between 500 Hz and 32 kHz) were presented randomly over time (independent Poisson process for each frequency with a rate of 2 Hz and a 50-ms dead time designed to prevent tones of the same frequency from overlapping in time).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…STRFs were obtained from 180-s multitone pip stimuli (Blake and Merzenich 2002;Catz and Noreña 2013;deCharms et al 1998;Gourévitch et al 2009;Noreña et al 2008;Valentine and Eggermont 2004). Tone pips (49 frequencies, 8 frequencies per octave covering 6 octaves between 500 Hz and 32 kHz) were presented randomly over time (independent Poisson process for each frequency with a rate of 2 Hz and a 50-ms dead time designed to prevent tones of the same frequency from overlapping in time).…”
Section: Methodsmentioning
confidence: 99%
“…First, we further investigated the effects of spectral notch depth to determine whether edge enhancement could be seen for spectral contrasts as small as 10 dB. Second, the edge enhancements described in our previous study (Catz and Noreña 2013) were observed after a 180-s presentation of the AFB stimulus. This is relatively fast but still too slow to dynamically shape the representation of real acoustic environments, which can vary on much smaller (fractions of a second) timescales (Singh and Theunissen 2003).…”
mentioning
confidence: 95%
See 3 more Smart Citations